Flattening experience: song lyrics and evaluation of crisis. Issue 2 (3rd April 2017) - Williams, Lawrence H.
ABSTRACT: How do people move on after moments of crisis? Using a form of modern folklore – "trance" music, and specifically songs that deal with break-ups and pain – as a medium for engaging with the narratives individuals recite when contemplating their lives, I use song lyrics as a tool for exploring how people both interpret and navigate their way through crises. Taking a theoretical stance inspired by Carl Jung, Soren Kierkegaard and American Pragmatism, I argue that the lyrics of trance music expose the ways in which individuals flatten their varied experiences into a single dimension of meaning in order to both make sense of their lives and, crucially, plan their next steps while experiencing moments of crisis. Seeing this process of flattening experience gives researchers and service providers new means for exploring how and why individuals may seek to "escape" their problems and delve into trance-like or, flattened, states.